Bloom Network: Seasonality in the lives of flower market actors and the networks formed in the Dangwa flower economy - Costa, Alyssandra Mariel; Villaraza, Aundrei Raphael (anthropozine: The Official Publication of the University of the Philippines H. Otley Beyer Museum of Anthropology; Vol 1 No 2 (2023): The Flow of Things and Bodies: The Production of Flowers in La Trinidad, Benguet, 2025)
Through on-ground site visits and interviews in the flower market in Dangwa, Sampaloc, Manila, the research looks at the network of lines of human and nonhuman actors as they intersect, engage, and entangle social and material life, discussing which months flower-buying usually peaks and the specific occasions that significantly affect the flower demand; how seasons manifest in the daily lives of the human actors involved; and the networks that are established and maintained in the whole enterprise.